K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a: Ta có: \(\widehat{DME}=\widehat{B}\)

\(\widehat{B}=\widehat{C}\)(ΔABC cân tại A)

Do đó: \(\widehat{DME}=\widehat{C}\)

Ta có: \(\widehat{EMC}+\widehat{C}+\widehat{MEC}=180^0\)

\(\widehat{EMC}+\widehat{DME}+\widehat{DMB}=180^0\)

mà \(\widehat{C}=\widehat{DME}\)

nên \(\widehat{MEC}=\widehat{DMB}\)

Xét ΔMEC và ΔDMB có

\(\widehat{MEC}=\widehat{DMB}\)

\(\widehat{C}=\widehat{B}\)

Do đó: ΔMEC~ΔDMB

c: Ta có: ΔBMD~ΔCEM

=>\(\dfrac{MB}{EC}=\dfrac{BD}{MC}\)

=>\(BD\cdot EC=MB\cdot MC=MB^2\)